The effect of integrated pest management on Scirpophaga innotata population and natural enemies on rice field in South Sulawesi, Indonesia - Rahmawasiah Rahmawasiah; Abdul Latief Abadi; Gatot Mudjiono; Akhmad Rizali (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rahmawasiah, Abadi AL, Mudjiono G, Rizali A. 2022. The effect of integrated pest management on Scirpophaga innotata population and natural enemies on rice field in South Sulawesi, Indonesia. Biodiversitas 23: 4510-4516. White rice stem borer, Scirpophaga innotata, is an important pest on rice plants that needs attention because the population is quite large in Luwu Raya. This pest attacks rice plants at all growth stages and can result in yield losses in rice production. Synthetic insecticides are a common control technique used by farmers to control these pests. The continuous use of pesticides will certainly have a negative impact. Therefore, pursuing effective control strategies and maintaining environmental sustainability is necessary. This study aimed to determine the white rice stem borer population and its natural enemies on rainfed land, and permanent irrigated lands managed conventionally and integrated pest management. The research was carried out using insect sampling techniques and calculating the white rice stem borer population and natural enemies in rice cultivation. In rainfed and irrigated rice fields, rice cultivation was carried out using conventional methods and integrated pest management (in the form of planting refugia and regulating the use of synthetic pesticides). The sampling was carried out on plants from the vegetative phase to the generative phase. The type of insect taken was the white rice stem borer in the form of collecting groups of eggs and larvae. Imago was observed visually and using a farmcop. In addition, the collection of natural enemy insects on the plantation was also carried out. The results showed that the application of the integrated pest management system caused no significant effect on the decline of the white rice stem borer population in both rainfed and permanently irrigated lands in Luwu Raya. The white rice stem borer population was more commonly found in rainfed land than permanently irrigated land. The parasitoids found were Telenomus rowani, Tetrastichus schoenobii and Trichogramma japonicum. The population of Telenomus rowani was more numerous than other types of parasitoids. On average, the parasitoid population was more in the land managed by integrated pest management (IPM) application than the conventionally managed land. The predators found on the land were Oxyopes javanus, Agriocnemis femina, Conocephalus longipennis, Menochilus sexmaculata, Ophionea nigrofasciata, Micraspis lineata, and Paederus fuscipes. Predator populations were more on land managed with the application of IPM than on land managed conventionally.